A cytokine-induced spheroid-based in vitro model for studying osteoarthritis pathogenesis - Scalzone, Annachiara; Cerqueni, Giorgia; Wang, Xiao Nong; Dalgarno, Kenny; Mattioli-Belmonte, Monica; Ferreira-Duarte, Ana M.; Gentile, Piergiorgio (Frontiers in Bioengineering and Biotechnology, 2023)
Given the lack of in vitro models faithfully reproducing the osteoarthritis (OA) disease on-set, this work aimed at manufacturing a reliable and predictive in vitro cytokine-based Articular Cartilage (AC) model to study OA progression. Cell spheroids of primary human fetal chondrocytes (FCs) and h-TERT mesenchymal stem cells differentiated chondrocytes (Y201-C) were analysed in terms of growth kinetics, cells proliferation and apoptosis over 10 days of culture, in healthy condition or in presence of cytokines (interleukin-1ß, −6 and TNF-α). Then, the spheroids were assembled into chondrospheres using a bottom-up strategy, to obtain an in vitro cytokines-induced OA model. The resulting chondrospheres were evaluated for gene expression and anabolic ECM proteins. Compared to the healthy environment, the simulated OA environment induced chondrocyte hyperproliferation and apoptotic pathway, decreased expression of anabolic ECM proteins, and diminished biosynthetic activity, resembling features of early-stage OA. These characteristics were observed for both Y201-C and HC at high and low concentrations of cytokines. Both HC and Y201-C demonstrated the suitability for the manufacturing of a scaffold-free in vitro OA model to facilitate studies into OA pathogenesis and therapeutic strategies. Our approach provides a faithful reproduction of early-stage osteoarthritis, demonstrating the ability of obtaining different disease severity by tuning the concentration of OA-related cytokines. Given the advantages in easy access and more reproducible performance, Y201-C may represent a more favourable source of chondrocytes for establishing more standardized protocols to obtain OA models.